Determination of Suitable Water Salinity and Live Food in The Rearing of Eel (Anguilla bicolor) Fry - Sutrisno, . (Jurnal Akuakultur Indonesia, 2008)
This study was conducted to determine suitable water salinity and live food in the rearing of eel,  Anguilla bicolor fry.  Eel fry in weight of 0.15±0.008 g/tail were reared at controlled tank at density of 2 fish liter-1 for 42 days.  Experiment was devided into two steps.  In the first step of experiment, eel fry were reared at different water salinity, i.e., 0; 5; 10 and 15 ppt.  Fish were fed on Tubifex at satiation.  The best result from the first experiment was then used in the second step of study to examine proper live food for eel fry.  Fish were fed on live food (Tubifex, Artemia, or Spirulina) at 10% body weight.  Survival rate, specific growth rate and food conversion ratio were observed.  The result of experiment showed that survival rate of eel fry reared in water salinity of 5 ppt (100%), 10 (96%) and 15 ppt (97%) was higher (p